Teacher Performance Evaluation Decision Support System Using Simple Additive Weighting: Case Study Mentari Intercultural School - Dery Afrizal Darmawin; Raymond Sunardi Oetama (Universitas Islam Raden Rahmat, Malang, 2023)
The role of the teacher is critical in the process of developing a country's resources. In this case, efforts are required to maintain teacher quality. Evaluating teacher performance is one method of maintaining the quality of these teachers. However, many teacher performance evaluation processes are still carried out manually in Indonesian schools. The solution to this problem in this study is the creation of a teacher performance evaluation system in the form of a web-based Decision Support System prototype by applying Simple Additive Weighting. Several pieces of software, including Java, Hypertext Markup Language, PHP, and Cascading Style Sheets, are used in this study. As a result, this system contributes to the simplification of the teacher evaluation process.